1997
DOI: 10.1523/jneurosci.17-23-09010.1997
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Changes in the Ca2+-Exocytosis Relationship during Repetitive Pulse Protocols in Bovine Adrenal Chromaffin Cells

Abstract: Stimulus-secretion coupling was monitored with capacitance detection in bovine chromaffin cells recorded in perforated patch mode and stimulated with trains of depolarizing pulses. A subset of stimulus trains evoked a response with a Ca 2ϩ -exocytosis relationship identical to that obtained for single depolarizing pulses (Engisch and Nowycky, 1996). Other trains evoked responses with enhanced or diminished Ca 2ϩ efficacy relative to this input-output function. The probability of obtaining a particular Ca 2ϩ -e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 51 publications
8
67
0
Order By: Relevance
“…Capacitance increases reflect the insertion of chromaffin granule membrane into the plasma membrane upon exocytosis. A relationship between the cumulative capacitance increase and total Ca 2ϩ influx has been demonstrated by Nowycky and colleagues (53,54).Virtually the identical quantitative relationship was observed in control transfected cells in our experiments (Fig. 8A, open circles) and in the previous work (Fig.…”
Section: Expression Of Ph-gfp Inhibits Exocytosis-ifsupporting
confidence: 90%
“…Capacitance increases reflect the insertion of chromaffin granule membrane into the plasma membrane upon exocytosis. A relationship between the cumulative capacitance increase and total Ca 2ϩ influx has been demonstrated by Nowycky and colleagues (53,54).Virtually the identical quantitative relationship was observed in control transfected cells in our experiments (Fig. 8A, open circles) and in the previous work (Fig.…”
Section: Expression Of Ph-gfp Inhibits Exocytosis-ifsupporting
confidence: 90%
“…Findings compatible with this hypothesis are that (1) the increase in cytosolic [Ca 2ϩ ] produced by a given stimulus is smaller in adrenal chromaffin cells studied with perforated patch recordings than in cells dialyzed by whole-cell recording (Engisch et al, 1997), and (2) mitochondrial contributions to Ca 2ϩ regulation are more evident in intact than in dialyzed retinal bipolar terminals (Zenisek and Matthews, 2000). The polyamine spermine increases mitochondrial Ca 2ϩ uptake (Lenzen et al, 1986), and Murphy et al (1996) found that overexpression of Bcl-2 in a neural cell line enhanced both the maximal Ca 2ϩ uptake capacity of mitochondria and the ability of mitochondria to sequester large quantities of Ca 2ϩ without undergoing profound respiratory impairment.…”
Section: ؉mentioning
confidence: 65%
“…We next performed additional experiments using more subtle physiological stimulations (Seward and Nowycky, 1996;Engisch et al, 1997;Chan and Smith, 2001). We applied either trains of action potentials or trains of short depolarization pulses (30 pulses of 10 -40 ms each at 4 Hz).…”
Section: Ubmunc13-2mentioning
confidence: 99%